Agarwood Inhibits Histamine Release from Rat Mast Cells and Reduces Scratching Behavior in Mice Effect of Agarwood on Histamine Release and Scratching Behavior - Eiji Inoue; Yasuharu Shimizu; Ryo Masui; Tomoe Tsubonoya; Tomomi Hayakawa; Keiichi Sudoh (Korean Pharmacopuncture Institute, 2016)
Objectives: This study was conducted to clarify the effects of agarwood on histamine release from mast cells in rats and on the scratching behaviors in mice. Methods: Histamine release from rat mast cells induced by compound 48/80 or concanavalin A (Con A) and compound 48/80-induced scratching behavior in mice were examined to investigate